2004
DOI: 10.7589/0090-3558-40.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Fecal Corticosterone in Sandhill Cranes During a Human-Led Migration

Abstract: Fourteen captive-reared greater sandhill cranes (Grus canadensis tabida) were conditioned to follow ultralight aircraft to promote migration between Wisconsin and Florida (USA) after release. Fecal samples were collected throughout the training period in Wisconsin and during a 1,977-km human-led migration to Florida to determine fecal corticosterone (FC) concentrations by radioimmunoassay. The mean (ϮSE) FC concentration during the training period was 109.5Ϯ7.5 ng/g and was representative of baseline levels re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The predominant avian glucocorticoid (GC) is corticosterone, a hormone released in response to a potential threat to homeostasis that is used to regulate behavior and suppress bodily processes that are nonessential to survival [Wingfield, ]. Levels of circulating GC are considered a reliable indicator of stress levels in birds [Dehnhard et al., ; Hartup et al., ]. Traditional measuring of GC concentrations in plasma requires handling and blood collection, which may be undesirable as restraint itself induces stress [Goymann, ; Mostl et al., ; Touma and Palme, ] and can cause a substantial rise in GC concentrations in the blood after two or three minutes [Hiebert et al., ; Romero and Reed, ].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The predominant avian glucocorticoid (GC) is corticosterone, a hormone released in response to a potential threat to homeostasis that is used to regulate behavior and suppress bodily processes that are nonessential to survival [Wingfield, ]. Levels of circulating GC are considered a reliable indicator of stress levels in birds [Dehnhard et al., ; Hartup et al., ]. Traditional measuring of GC concentrations in plasma requires handling and blood collection, which may be undesirable as restraint itself induces stress [Goymann, ; Mostl et al., ; Touma and Palme, ] and can cause a substantial rise in GC concentrations in the blood after two or three minutes [Hiebert et al., ; Romero and Reed, ].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The authors recommended that translocation events should include frequent breaks in a dark, cool environment with ample water and be restricted to outside of the reproductive period. Hartup et al [57] assessed the effects of human-guided migration of sandhill crane Grus canadensis tabida and revealed that fecal corticosterone levels were consistent with levels observed in other migrants, suggesting that this conservation strategy does not impart undue stress and is potentially a viable option for other imperiled species such as whooping cranes Grus americana. However, the lack of a corticosterone response does not always indicate a lack of stress (Box 1).…”
Section: Box 1 Physiological Assessment Of Environmental Stressorsmentioning
confidence: 99%
“…The quantification of fecal corticoids is a useful non-invasive tool for the assessment of stress in birds (Shepherdson, Carlstead & Wielebnowski, 2004). The predominant glucocorticoid in birds is corticosterone, a hormone released in response to a potential threat to homeostasis, which is used to regulate behaviour and suppress body processes that are nonessential to survival (Wingfield, 1994), and the levels of circulating glucocorticoids are considered a reliable indicator of stress levels in birds (Dehnhard et al, 2003;Hartup et al, 2004). Like cortisol in mammals, corticosterone levels can be interpreted as an adaptive response to stressful events.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of glucocorticoid concentrations is increasingly being applied to zoo animals thorough the sampling of urine, feces and saliva, and this methodology can provide a very useful longitudinal measure of the adrenal output to detect potentially indicative patterns of chronic stress, even in birds (Shepherdson et al, 2004), and associated with behavioral and physiological changes in energy demand (Harvey et al 1984). Furthermore, the levels of circulating corticosterone are considered a reliable indicator of stress levels in birds (Dehnhard et al, 2003;Hartup et al, 2004), although blood sampling can be inappropriate because its high invasiveness can cause stress responses (Nemeth et al, 2016), thus compromising the stress assessment (Hamilton & Weeks, 1985;Le Maho et al, 1992). The non-invasive glucocorticoid measurement, especially when used in conjunction with other parameters, such as behavior, can give an accurate and important insight into the welfare status of an individual or a group of animals (Lane, 2006).…”
Section: Introductionmentioning
confidence: 99%